Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3174/ajnr.a1312
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics in a Lethal Basilar Artery Aneurysm Just before Its Rupture

Abstract: BACKGROUND AND PURPOSE:Hemodynamics is thought to play an important role in the mechanisms of cerebral aneurysm initiation, progression, and rupture. The purpose of this study was to present a hemodynamic study of a cerebral aneurysm immediately before its rupture to assess whether previously identified hemodynamic characteristics would classify this aneurysm in the high-risk category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 13 publications
(10 reference statements)
7
37
0
Order By: Relevance
“…Accordingly, the best way to evaluate the rupture risk of IA is to study the aneurysm in the ready-to-rupture state. A few cases of gross blood-flow characteristics of IA just before rupture have been reported, 14,15 but without comparison with ruptured aneurysms. The exact morphology and hemodynamics just before aneurysm rupture are not clear yet, but both studies of aneurysms before their rupture demonstrated low WSS on the aneurysm sacs.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the best way to evaluate the rupture risk of IA is to study the aneurysm in the ready-to-rupture state. A few cases of gross blood-flow characteristics of IA just before rupture have been reported, 14,15 but without comparison with ruptured aneurysms. The exact morphology and hemodynamics just before aneurysm rupture are not clear yet, but both studies of aneurysms before their rupture demonstrated low WSS on the aneurysm sacs.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,44,52,56 Impinging zones and areas of high WSS were correlated to aneurysm rupture. 5 The histological study of Meng et al 32 also shows that destructive remodeling involving loss of smooth muscle cells occurs at the region of high WSS and WSS gradient, where the flow accelerates near the impinging area. Therefore, we examine the flow pattern in the infundibulae, WSS/pressure distributions in the PCoA region, and the effect of widened root of a branch on the impinging patten using patient-specific infundibulum and aneurysm geometries.…”
Section: Introductionmentioning
confidence: 96%
“…[2][3][4] CFD simulations have been used to gain insight into the patient-specific hemodynamics and could potentially assist rupture-risk assessment [5][6][7][8][9] and treatment planning. [10][11][12][13][14][15][16] Vascular models can be constructed through segmentation of 3DRA and CTA images.…”
mentioning
confidence: 99%